2017
DOI: 10.24036/ld.v10i2.7197
|View full text |Cite
|
Sign up to set email alerts
|

The Systemic Functional Linguistics: The Appropriate and Inappropriate Use of Devices in Students’ Academic Text

Abstract: Indonesia eThis qualitative research was conducted to describe the types of grammatical cohesive devices and to compare the frequency of using the appropriate and inappropriate of those devices used by students in composing analytica chosen conveniently by selecting only 34 students of grade two of SMAN 7 Padang. The data was collected from the analytical exposition texts written by them. The result of this research shows that the able to use the grammatical cohesive devices in variant ways. Those four types f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…However, both were seen employed in middle achievers' texts as many as three and two items respectively whilst also identified in high achievers' texts for as many as nine and four items. This finding corresponds to the phenomena observed by Adiantika (2015), Arianto et al (2017), andMalombassang (2018). The fact that both could be established in middle and high but not in low achiever texts is due to its complexity and challenging factor as they are commonly used to make spoken communication effective (Halliday & Matthiessen, 2004).…”
Section: Substitution and Ellipsissupporting
confidence: 91%
See 2 more Smart Citations
“…However, both were seen employed in middle achievers' texts as many as three and two items respectively whilst also identified in high achievers' texts for as many as nine and four items. This finding corresponds to the phenomena observed by Adiantika (2015), Arianto et al (2017), andMalombassang (2018). The fact that both could be established in middle and high but not in low achiever texts is due to its complexity and challenging factor as they are commonly used to make spoken communication effective (Halliday & Matthiessen, 2004).…”
Section: Substitution and Ellipsissupporting
confidence: 91%
“…Furthermore, similar to Albana et al (2020), Malombassang (2018), and Sari et al (2018), this study also reported that reference was the most widely used cohesive devices when it came to grammatical cohesion items (24.2%) followed by conjunctions in the second place (11.5%). This finding strengthens other studies showing that reference has a huge role in minimizing redundant repetition of words in students' analytical exposition text (Arianto et al, 2017;Halliday & Matthiessen, 2004). Doing so, the arguments and evidence provided by the students could be easily understood by the readers.…”
Section: Referencesupporting
confidence: 90%
See 1 more Smart Citation
“…Great number of Indonesian well-known academics view SFL as a pedagogical mandate for resolving student issues in second language writing classes and further reinforce their adherence to its received wisdom (Agustien, 2016;Arianto et al, 2017;Aunurrahman et al, 2017;Cahyono, 2018;Dewi, 2016;Emilia, 2016;Emilia & Hamied, 2015;Kuswanto, 2015;Lestariningsih, 2020;Putra & Lukmana, 2017;Widodo, 2018). However, Indonesian researcher's lens obscures classroom reality and misses the perspective of students who are confronted with the task of learning to communicate competently in a foreign language and go through pedagogical process (Lian, 2000).…”
Section: Introductionmentioning
confidence: 99%